Pakaian Terbaik Menurut Al-Qur’an (Telaah Maudhu’i atas Term-Term Bermakna Pakaian dalam al-Qur’an) - Sugirma Sugirma; Agustang K (IAIN TERNATE, 2022)
In the Qur'an there are several terms regarding clothing, namely libas, tsiyab, sarabil, qamis, jalabib, khumur and risy. The seven terms referred to as clothing in the Qur'an consist of two categories, namely clothing in the essential sense (related to the body), and clothing in the majazi sense (related to spiritual and psychological). This research is a qualitative research using descriptive analysis. All data and information were collected through searching related literature by utilizing online media and relevant literature sources, with the Qur'an as the primary data source. Data analysis was carried out by examining the information that had been obtained using the Maudhu'i approach, then providing an argument that was considered relevant, then drawing a conclusion on the problems that had been discussed. The results obtained from this study are that the Qur'an offers the best concept of clothing that a Muslim must have. The best clothes in question are in QS. Al-Araf: 26 is the attitude and character of a Muslim who is attached to him. The clothes are not only wrapped around the body and cover the genitals, but also a reflection of their morals. So, a pious Muslim does not only pay attention to the beauty or tidiness of the outer clothing that wraps his body, but also pays attention to the beauty of the morals that binds his soul and heart. He will always surrender to Allah Subhanahu wata'ala, carry out His commands, and stay away from His prohibitions.